Worldwide research trends of pregnancy hypertension in epigenetics field - Yuan, Didi; Huang, Yangqing; Liu, Hanqi; Tang, Haotian; Liu, Junwen (Frontiers in Public Health, 2025)
IntroductionHypertension in pregnancy (HIP) poses significant health risks for both mothers and infants. Development of HIP is influenced by genetic and environmental factors, with epigenetic modifications partially explaining underlying mechanisms. Bibliometric tools aid researchers in quickly gaining insights into field dynamics and trends.MethodsIn this investigation, we conducted a search for relevant publications in the Web of Science Core Collection database using specific keywords. We employed Citespace and WOSviewer software for analysis of interconnections and co-occurrence of information across publications, countries, authors, institutions, keywords and cited literature. Ultimately, we identified 4,316 research papers on hypertension in pregnancy within the epigenetics domain (HIPE).ResultsOur analysis revealed that China had the highest number of publications (n = 1,353, 31.35%), while the University of Melbourne was the most prolific institution (n = 107, 2.48%). Among author analysis, Tong S emerged as highly productive (n = 41, 0.95%). Preeclampsia (PE) emerged as being extensively studied among various types of HIP. High-frequency keywords associated with HIP mechanisms included oxidative stress, proliferation, apoptosis and invasion. Regarding epigenetics-related terms, DNA methylation, mRNA and ncRNA exhibited distinct heat burst periods. The number of HIPE papers demonstrated an upward trend observed through three stages of growth.DiscussionOur bibliometric-based study provides novel insights into current research progress on HIP from an epigenetic perspective, serving as a source of new ideas and inspiration for future investigations of HIP diseases.